Double electron capture searches in 74Se. (28th June 2016) - Lehnert, B; Wester, T; Degering, D; Sommer, D; Wagner, L; Zuber, K
Abstract: A search for various double electron capture modes of 74 Se has been performed using an ultralow background Ge-detector in the Felsenkeller laboratory, Germany. Especially for the potentially resonant transition into the 1204.2 keV excited state of 74 Ge a lower half-life limit of 0.70 × 10 19 yr (90% credibility) has been obtained. Serious concerns are raised about the validity of obtained 74 Se limits in some recent publications.